Thomas H. Robbins papers - Robbins, Thomas H. (Thomas Hinckley), 1900-1972.
Correspondence, duty orders, logbooks, biographical material, speeches, and other papers documenting Robbins's naval career and emphasizing his specialty in naval aviation. Subjects include aircraft; aircraft companies; espionage; European politics; foreign navies, naval activities, ships, and armaments; and the U.S. Navy and naval activities. Includes Robbins's personal operations diary, narratives, and newspaper articles relating to the role of the minesweeper Sandpiper in the Aleutian Islands survey expedition (1933-1935).
U.S. naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: United States. -- Navy; United States. -- Navy -- Aviation; Sandpiper (Minesweeper); Aeronautics; Aircraft industry -- Military aspects; Airplanes, Military; Military intelligence; Military weapons; Naval aviation; Naval history, Modern -- 20th century; Navies; Warships; Aleutian Islands (Alaska) -- Surveys; Europe -- Politics and government; Naval officers